The effect of holding time on dissimilar resistance spot welding of stainless steel 316L and Ti6Al4V titanium alloy with aluminum interlayer - Taufiqurrahman, I. (Elsevier Ltd, 2020)
A combination of stainless steel and titanium alloy is obviously a good choice for the industrial application using resistance spot welding process. However, to provide good quality of the welded joint was difficult due to the different types of materials. To enhance the weld quality, aluminum was placed in between stainless steel and titanium alloy as an interlayer. The mechanical and physical properties of the welded joint were investigated. The results of the SS316L/Ti6Al4V joint show that the tensile-shear load was 895N and the maximum hardness value was 367.3 HV under the weld current of 12 kA, welding time and holding time of 10 cycles and electrode force of 4 kN. The microstructure result shows that a very thin reaction layer was formed on the intermetallic compound of the SS316L/AA5754 interface. Meanwhile, a diffusion-reaction has occurred on the interface of AA5754/Ti6Al4V during resistance spot welding. The effect of holding time was investigated due to the void appears in the middle of the weld nugget. The existence of the void will significantly reduce weld strength. The increase of holding time successfully remove the void and increase the weld strength of the joint under the tensile-shear test. Â© 2020 Elsevier Ltd. All rights reserved.